2017
DOI: 10.2196/cardio.7915
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Utility of a Novel SMS- and Phone-Based System for Blood Pressure Control in Hypertensive Patients: Feasibility Study

Abstract: BackgroundAlthough hypertension (HTN) is a major modifiable risk factor for arterial damage, blood pressure (BP) remains poorly controlled in the hypertensive population. Telemedicine is a promising adjunct intervention that may complement traditional therapies and improve adherence rates; however, current approaches have multiple barriers to entry, including the use of relatively expensive Bluetooth devices or the dependence on smart phone utilization, which tend to exclude low-income and more elderly populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Preliminary studies have shown that SMS text messaging and HBPM can be effective in promoting medication adherence and BP control [8][9][10][11]. When HBPM is used in the surveillance of hypertension, it is more cost effective than office visits in the long run, as it reduces the number of unnecessary return visits and antihypertensive drugs administered to chronic users [12].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have shown that SMS text messaging and HBPM can be effective in promoting medication adherence and BP control [8][9][10][11]. When HBPM is used in the surveillance of hypertension, it is more cost effective than office visits in the long run, as it reduces the number of unnecessary return visits and antihypertensive drugs administered to chronic users [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although using the GPRS channel eases the transmission (due to the simplicity of implementation), the internet connection stability on a mobile device varies with location, and disconnections from the internet may occur more often than a voice call. Another method to send the data in specified time intervals is via short message service (SMS) [4,[6][7][8][9][10]. However, SMS-based data transmission does not support any continuous connection and data are transmitted at some certain intervals [11].…”
Section: Introductionmentioning
confidence: 99%